2023
DOI: 10.3390/a16040176
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Analysis of Brain Tumor Detection from MR Images Using Deep Learning Networks

Abstract: Creating machines that behave and work in a way similar to humans is the objective of artificial intelligence (AI). In addition to pattern recognition, planning, and problem-solving, computer activities with artificial intelligence include other activities. A group of algorithms called “deep learning” is used in machine learning. With the aid of magnetic resonance imaging (MRI), deep learning is utilized to create models for the detection and categorization of brain tumors. This allows for the quick and simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Comparing this proposed classifier with existing studies, Saeedi et al [ 41 ] achieved an accuracy of 96.46%, demonstrating slightly lower performance than the proposed model. Kalam et al [ 42 ] and Mahmud et al [ 62 ] also reported accuracies of 98.35% and 93.53%, respectively, placing them in line with or slightly below the proposed classifier. Woźniak et al [ 63 ] obtained an accuracy of 96.46%, and Reyes et al [ 64 ] achieved an accuracy of 98.03%.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Comparing this proposed classifier with existing studies, Saeedi et al [ 41 ] achieved an accuracy of 96.46%, demonstrating slightly lower performance than the proposed model. Kalam et al [ 42 ] and Mahmud et al [ 62 ] also reported accuracies of 98.35% and 93.53%, respectively, placing them in line with or slightly below the proposed classifier. Woźniak et al [ 63 ] obtained an accuracy of 96.46%, and Reyes et al [ 64 ] achieved an accuracy of 98.03%.…”
Section: Resultsmentioning
confidence: 79%
“…Figure 9 shows the performance comparison of the various performance metrics, such as accuracy, precision, and recall, for four classes between the proposed and the existing models [ 41 , 42 , 62 , 63 , 64 ]. In the evaluation of various classifiers for brain tumor classification, the proposed classifier demonstrates commendable performance across multiple metrics.…”
Section: Resultsmentioning
confidence: 99%
“… Mahmud, M.I. et al, (2023) [ 3 ] A collection of 3,264 MRI brain tumor images, encompassing categories such as Glioma, Meningioma, Pituitary, and No tumor. 98.43% Implement deep learning with a CNN architecture to identify and classify brain tumors and compare the results with those obtained using transfer learning models like ResNet-50, VGG16, and Inception V3.…”
Section: Related Workmentioning
confidence: 99%
“…This demonstrates the effectiveness of LBP features and CNN models for accurate brain tumor classification in MRI images. Mahmud et al ( 2023 ) employed a CNN model for brain tumor classification on a relatively large dataset of 3264 MRI images. The CNN model was trained to learn discriminative features and classify the input images into different tumor categories.…”
Section: Literature Reviewmentioning
confidence: 99%